Evaluation of the relationship between nurses' attitudes towards futile treatments and their ethical attitudes: A cross-sectional and analytical study - Andi, Senem; Akcoban, Sumeyye; Gungor, Serap; Gider, Neslihan Yağmur; Tosun, Betül; Dirgar, Ezgi (John Wiley and Sons Inc, 2025)
Background: Futile treatments waste health resources and may conflict with nurses' ethical attitudes, causing moral distress. Nurses frequently administer such treatments due to external pressures. Desing and Methods: This cross-sectional study involved 205 nurses in a public hospital in Turkey (June–August 2024). Data were collected using the “Nurse Descriptive Information Form,” “Nurses' Attitudes Towards Futile Treatment Scale (NAFTS),” and “Ethical Attıtude Scale in Nursıng Care (EASNC).”. Results: The mean age of participants was 33.62 ± 7.37 years; 69.8% were female, and 37.1% worked in intensive care. While 90.7% received ethics training, 54.6% lacked knowledge about futile treatments. Over half (54.1%) had administered care they considered futile, with 82.9% citing physician orders as the main reason. Most (70.7%) saw futile treatments as an ethical issue. The NAFTS mean score was 40 ± 7.67 (medium level), and the EASNC score was 158.60 ± 14.85 (high level). A moderate negative correlation (r = −0.394, p < 0.05) indicated that stronger ethical attitudes reduced acceptance of futile treatments. Conclusion: As nurses' ethical attitudes strengthened, their tendency to administer futile treatments decreased. Setting realistic, patient-specific care goals can prevent ethical conflicts and unhelpful care. Implications for the Profession: Providing ethical training is essential to help nurses avoid futile treatments and make better decisions in challenging situations. Developing supportive policies in healthcare institutions can guide ethical practices and reduce unnecessary treatments. Improving work conditions, such as adjusting hours and reducing workloads, enhances nurses' ability to focus on ethical and patient-centered care. Encouraging teamwork between nurses and doctors strengthens communication and shared decision-making, minimising conflicts. Additionally, reducing futile treatments not only saves healthcare resources but also improves the quality of patient care and professional satisfaction for nurses. These measures collectively support the nursing profession and contribute to better healthcare outcomes. Reporting Method: We adhered to the STROBE. No Patient or Public Contribution: Given that this study is based on the literature, namely the codes of ethics, there is no direct/indirect involvement of patients or the public. © 2025 The Author(s). Scandinavian Journal of Caring Sciences published by John Wiley & Sons Ltd on behalf of Nordic College of Caring Science.
Keywords: ethical attitudes; futile treatment; medical futility; nurses; nursing ethics